The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1186/s40463-017-0187-1
|View full text |Cite
|
Sign up to set email alerts
|

The Hippo component YAP localizes in the nucleus of human papilloma virus positive oropharyngeal squamous cell carcinoma

Abstract: BackgroundHPV infection causes cervical cancer, mediated in part by the degradation of Scribble via the HPV E6 oncoprotein. Recently, Scribble has been shown to be an important regulator of the Hippo signaling cascade. Deregulation of the Hippo pathway induces an abnormal cellular transformation, epithelial to mesenchymal transition, which promotes oncogenic progression. Given the recent rise in oropharyngeal HPV squamous cell carcinoma we sought to determine if Hippo signaling components are implicated in oro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 42 publications
2
18
0
Order By: Relevance
“…However, there are also non-canonical pathways that promote nucleus-translocation of YAP/TAZ, and thus stimulate its transcriptional activities, through which YAP/TAZ plays important tumor-promoting roles in a number of cancers (53). Several studies have also showed that aberrant YAP accumulation in the nucleus of cancer cells was found in both cervical cancer and HPV-positive OSCC, and HPV-positive patients with higher YAP levels usually had a more advanced stage (54)(55)(56). Moreover, Webb Strickland and colleagues have reported that E6 oncoprotein could associate with cellular PDZ domain proteins to promote the nuclear localization of YAP (57).…”
Section: Discussionmentioning
confidence: 99%
“…However, there are also non-canonical pathways that promote nucleus-translocation of YAP/TAZ, and thus stimulate its transcriptional activities, through which YAP/TAZ plays important tumor-promoting roles in a number of cancers (53). Several studies have also showed that aberrant YAP accumulation in the nucleus of cancer cells was found in both cervical cancer and HPV-positive OSCC, and HPV-positive patients with higher YAP levels usually had a more advanced stage (54)(55)(56). Moreover, Webb Strickland and colleagues have reported that E6 oncoprotein could associate with cellular PDZ domain proteins to promote the nuclear localization of YAP (57).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have also showed that aberrant YAP accumulation in the nucleus of cancer cells was found in both cervical cancer and HPV-positive OSCC, and HPV-positive patients with higher YAP levels usually had a more advanced stage (60)(61)(62). Moreover, Webb Strickland and colleagues have reported that E6 oncoprotein could associate with cellular PDZ domain proteins to promote the nuclear localization of YAP (63).…”
Section: Discussionmentioning
confidence: 99%
“…The PI3K-PDK1 pathway integrates signals from fibronectin, LPA, GPCR receptors and EGFR [68]. Interestingly, despite the fact that nuclear YAP localization has been described in oropharyngeal HPV positive tumors [89], Hippo pathway alterations and in particular FAT1 inactivation or YAP amplification are not frequent events in HPV positive HNSCC [10] (Figure 3). Although further research into the role of the Hippo-YAP pathway in this tumor subtype is needed, it is tempting to speculate that other mechanisms might lead to YAP activation.…”
Section: The Hippo-yap Pathway In Hnsccmentioning
confidence: 99%